Identification and critical phenomenon studies of polymorphic phases in binary intermetallic compound DyIr3. (May 2020) - Mondal, Binita; Dan, Shovan; Mondal, Sudipta; Bhowmik, R.N.; Ranganathan, R.; Mazumdar, Chandan
Abstract: The rare-earth and transition-metal based polycrystalline, binary compound DyIr 3 has been synthesized successfully and is found to form as a macroscopic coexistence of AuBe5 and AuCu 3 -type polymorphic structures. The analysis of dc magnetization and specific heat data reveals that among the two polymorphic phases, the AuBe5 -type phase exhibits ferromagnetic ground state below 22 K, while AuCu 3 -type phase shows paramagnetic behaviour down to 2 K. The detail studies of magnetic relaxation, magnetic memory effect and frequency dependency of ac magnetic susceptibility establish the presence of glassy phase in the system. The critical behaviour have been investigated for DyIr 3 in detail in the vicinity of its magnetic transition temperature by means of dc magnetization, specific heat data, Arrott–Noakes plot, Kouvel–Fisher plot, critical isotherm, and magnetocaloric study. The type of magnetic universal class, in which DyIr 3 belongs, has been identified through the critical behaviour study. Highlights: Synthesis of intermetallic compound DyIr 3 with coexisting polymorphic structure. It exhibits spin-glass behaviour below its ferromagnetic phase transition. Critical exponent values confirm that DyIr 3 lies in tricritical mean-field class. Magnetic universal class of DyIr 3 has been verified from the magnetocaloric study.